Impact of root-stem coupling damage from mechanical transplanting on the growth of large rice seedlings - Wang, Tingjue; Sun, Dongdong; Xiong, Wei; Kuang, Fuming; Xue, Kang; Shi, Menghao; Xi, Dongdong; Zhu, Dequan (Plant growth regulation, 2024)
The mechanical transplantation of large rice seedlings severely inhibits yield; however, studies on the impacts of mechanical transplantation are relatively scarce. Root–stem coupling damage is the main form of damage in mechanically transplanted large seedlings. Here, 40-day-old rice seedlings served as subjects for pot experiments conducted under two conditions, with and without a root–stem coupling damage treatment. Changes in root characteristics, leaf SPAD values, and stem structure were observed at 12 days after transplantation. Additionally, a transcriptome analysis was conducted on the seedlings 6 days post-transplantation. The root–stem coupling damage significantly inhibited rice growth. By 12 days after planting, the root length, root surface area, root volume, number of root tips, and SPAD values in the treatment group decreased by 44.4%, 53.1%, 61.5%, 31%, and 23%, respectively, compared with the control (non-treatment) group. The heart leaf growth rate decreased by 49.5% between the 9th and 12th days after transplantation. Transcriptome sequencing data indicated that mechanical transplantation enhanced rice disease resistance and structural strength but slowed the growth rate. Adjustments in gene expression may help rice resist the physical and biological stresses encountered during mechanical transplantation. This study provides important references for the design of rice transplanters and the selection of suitable varieties for mechanical transplantation.